2021
DOI: 10.1155/2021/8685158
|View full text |Cite
|
Sign up to set email alerts
|

The Role of FSHR SNPs and AMH in Follicular Fluid and Serum in Ovarian Response during COS: A Pilot Study

Abstract: Background. Several studies have investigated on the polymorphism Ser680Asn of FSHR and its use as a predictive indicator of response to an IVF/ICSI protocol. Furthermore, measurement of AMH in serum and follicular fluid is a useful prognostic indicator for the outcome of an assisted reproduction attempt. The purpose of this study is to examine the FSH receptor Ser680Asn polymorphism in combination with AMH levels in both serum and follicular fluid, on the day of oocyte collection. Materials and Methods. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…However, in the literature, it was demonstrated that women carrying the Ser680 variant (homozygous specially) yield a lower number of mature oocytes recovered compared with patients who have at least one Asn680 residue [ 36 ]. Nevertheless, other authors found that in patients homozygous for Asn680, the number of mature oocytes is reduced compared to homozygotes for Ser680 [ 37 ]. Although, the absence of a relationship between the FSHr Asn680Ser genotype and the number of recoverable metaphase II oocytes was also reported [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the literature, it was demonstrated that women carrying the Ser680 variant (homozygous specially) yield a lower number of mature oocytes recovered compared with patients who have at least one Asn680 residue [ 36 ]. Nevertheless, other authors found that in patients homozygous for Asn680, the number of mature oocytes is reduced compared to homozygotes for Ser680 [ 37 ]. Although, the absence of a relationship between the FSHr Asn680Ser genotype and the number of recoverable metaphase II oocytes was also reported [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%